Bridging the gap: literacy clubs for underperforming grade 8 and 9 learners in a township school - Matariro, Mariyeni (My University, 2017)
Using English as a medium of instruction or the Language of Learning and Teaching (LoLT) can be a very difficult task especially if the children do not speak the language and are multilingual. It affects reading, writing and oral language skills. This study seeks to examine the impact of exposing underperforming grade 8 and 9 learners of English to a Literacy Club. The study is a follow up of the study that was done in 2013. The main difference between the current study and the previous study is that, participants in the first study were already readers and volunteered to join the Literacy Club. Although school rules were relaxed, only English was used to discuss the read texts. In the current study, because I was working with weak readers, learners who have been identified as at risk of failing and had all been invited to join the Literacy Club as a form of language enrichment programme, the participants will be allowed to use all the linguistic skills at their disposal for both discussion of texts and reflecting in their journals. This is based on the premise that being multilingual should not be viewed as a barrier but a resource for learning. Underpinned by the socio-cultural approach to learning and drawing intensively from different theoretical views of language learning and learning to read, a case of 16 learners in grade 8 and 9 participated in this study. The study adopted a qualitative approach where a number of methods were used for the purposes of data collection. The study discovered that Literacy Clubs are a good vehicle to impart reading skills as they motivate learners to read. Literacy Clubs also have a positive impact on attainment in language tests. The study also discovered that allowing learners to use all the linguistic repertoires available to them boosts their confidence to talk about the literature they have read and improves the quality of their discussions. The study recommended that reading should be allocated time within normal school hours for each grade, children should be given an opportunity to write reading journals which should be marked and commented on by the teacher to encourage free writing and develop writing skills, the context of the school should be considered when deciding on the language policy to adopt and lastly but most importantly, translanguaging should be seriously considered as a pedagogical tool when teaching a second language.
A thesis submitted to the School of Education, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements of the degree of Master of Arts In Applied Language Education and Literacy Studies , Johannesburg 2016
Keywords: Education--South Africa; Group reading--South Africa; English language--Study and teaching (Higher)--South Africa; Multicultural education--South Africa; Reading comprehension--South Africa